Secure and Lightweight Cryptographic Scheme for Iot Based Applications - Aakash, R.; M.B.Mukesh Krishnan, Dr. (International Journal of Engineering and Technology, 2018)
Internet of Things is a collection of devices like home appliances and automobiles considering anything that is fixed with electronics, software applications and sensors which can be used to bridge the gap between physical world and a computerised system allowing direct connections between the two thereby reducing the human efforts and provides future enhancements and other economic benefits. With the recent development in IOT and the increase in the usage of wireless technologies gives us a chance for growth in various applications like Education, Agricultural benefits and other Medical sectors. With the increase in the use of IOT with the incorporation of wireless technologies there is an increase in security threats against secrecy and privacy and are often prone to breaches that cause access points to those data vulnerable to attacks. Therefore we need an authentication scheme that is both energy efficient and not resource clogging which also provides methods to transfer data with no issues to confidentiality which is a major concern to the users. We need a lightweight cryptographic algorithm that offers protection against various attacks including Man in the Middle attack and Masquerading attacks.Â Â